In Pursuit of Offshore Wind: Financial, Political, Environmental, and Ethical Considerations - Anderson II, Erik; Cartwright, Sydnei; Dillahunt, Hannah; Dozier, Maria; Fazili, Osman; Salazar, Moira (2023)
In today's political and ecological climate, there is a growing demand for the Biden Administration to invest in renewable energy sources. Particularly, along the Atlantic, and Pacific coasts, and in the Gulf of Mexico, offshore wind is gaining traction as a viable alternative to fossil fuels. This is due to its technical capability to supply electricity beyond consumptive needs, and its availability to major cities in these regions. Yet, in the United States, there are just seven offshore wind turbines. Thus, to meet the national demand for renewable energy it is clear the US is going to need a lot more offshore wind capital. With this, offshore wind has come to the forefront of the energy economy to help meet demand. The Bureau for Ocean Energy Management (BOEM) is working with the National Oceanic and Atmospheric Administration (NOAA) to lease and permit tracts of the ocean for offshore wind development. Although it is an exciting time to be looking into the potential of offshore wind, there are many considerations that should be addressed to ensure the offshore wind industry develops with minimum possible negative impacts to the environment and is part of a responsible and just transition to a renewable energy economy. These considerations include: · protections and mitigations for marine mammals during offshore wind development’s pre-construction, construction, and operation phase, and decommissioning · the impact of the cost of those mitigations on the economic viability of offshore wind · policies that determine what measures should be taken, and · the social justice implications of offshore wind development. In this report we hope to shed light on these and other considerations. We have conducted an analysis of: • existing mitigation measures that are industry standard • the impacts of construction on the North Atlantic Right Whale (NARW) • Impact of mitigation measures on economic viability • policies that can improve protecting for NARW • the estimated cost of these protections, • the economic ...